Experimental Study on Concrete Strength by Partial Replacement of Fine Aggregate with Crumb Rubber - B.Manojkumar, S.Durga Lakshmi, P.R.Kalyana Chakaravarthy (International Journal of Advanced Science and Technology, 2020)
Crumb rubber is produced using tire chips.crumb rubber cement is forestall the natural pollution.so piece elastic cement is utilized for construction.in this study is utilized to the crumb rubber is halfway substitution of fine aggregate.the solid blend configuration is utilizing IS strategies for M20 level concrete.crumb rubber total rate is supplanting of fine total is 5%,10%,15% and 20%.slump,workability,compressive quality and flexural quality tests are lead. The rubberised concrete additionally indicated increment in sturdiness and improved bond between solid particles hence decreasing extraordinary breaking. Use of elastic tire totals, which is a waste item, in solid development is monetarily reasonable and ecologically compelling.